IQ-Hopping: Distributed Oblivious Channel Selection for Wireless Networks - Bhartia, Apurv; Chakrabarty, Deeparnab; Chintalapudi, Krishna; Qiu, Lili; Radunovic, Bozidar; Ramjee, Ramachandran (MobiHoc '16 Proceedings of the 17th ACM International Symposium on Mobile Ad Hoc Networking and Computing, Paderborn, Germany, 2016)
Interference in WiFi deployments is a growing problem due to the increasing popularity of WiFi. Therefore it is important that APs find the right channel to operate upon. Through a large scale measurement study involving over 10,000 WiFi APs we show that channel measurements and selection are most effective when performed frequently (every few minutes). This is because of the highly dynamic nature of WiFi traffic congestion. Our key contribution in this paper is a novel approach to distributed channel selection – Ineffective time Quantum (IQ) Hopping, that is simple enough to be described in three lines and has provable optimality guarantees. IQ-Hopping does not require any explicit channel measurements and can react within a matter of several seconds to bad channel conditions, including microwave ovens, hidden interferers, or dynamically varying congestion. Through implementation and experiments on off-the-shelf WiFi routers (OpenWRT, MadWiFi), we demonstrate the effectiveness of IQ-Hopping.